Sintilimab plus decitabine for higher-risk treatment-naïve myelodysplastic syndromes: efficacy, safety, and biomarker analysis of a phase II, single-arm trial - Jing Wang; Ying-Jun Chang; Xiaohong Liu; Wenjing Yu; Hao Jiang; Xiaojun Huang; Siqi Li; Xiaosu Zhao; Jinsong Jia; Xiaolu Zhu; Lizhong Gong (Journal for ImmunoTherapy of Cancer)
Background Immunotherapy combined with azacitidine was feasible in higher-risk myelodysplastic syndromes (MDSs) with limited sample size of treatment-naïve patients, while the optimization of treatment strategies, including the optimal immune checkpoint inhibitor and hypomethylating agent and possible benefiting population, remained undefined. This study first evaluates the efficacy and safety of sintilimab, a PD-1 blockade, plus decitabine in treatment-naïve higher-risk MDS patients and investigates biomarkers for predicting treatment response.Methods In this phase II, single-arm trial (ChiCTR2100044393), treatment-naïve higher-risk MDS patients with an International Prognostic Scoring System-Revised score >3.5 received sintilimab (200 mg, days 1 and 22) and decitabine (20 mg/m2, day 1–5) over 6-week cycles. The primary endpoint was the overall response rate (ORR), including complete remission (CR), partial remission (PR) or marrow CR.Results A total of 54 eligible patients were enrolled and treated, with 25 (46.3%) having very high-risk MDS. Among 53 evaluable patients, the ORR was 77.4% (n=41), including 26.4% CR (n=14). The overall clinical improvement rate (CR, PR, marrow CR or hematological improvement) reached 81.1%. With a median follow-up of 20.0 months, the median event-free survival was 23 months with 12 progressing to acute myeloid leukemia. Median overall survival was not reached. Treatment was generally well tolerated, with hematologic toxicities being the most common adverse events. Biomarker analysis highlighted a negative correlation between T cell exhaustion markers, particularly TIM-3 and PD-1, with ORR.Conclusions The combination of sintilimab and decitabine shows promise efficacy for higher-risk MDS, with a favorable safety profile. The potential predictive value of T cell exhaustion biomarkers might help screen the possible benefiting population.Trial registration number ChiCTR210044393.